The canine host serving as a sentinel species for tick-borne diseases caused by Anaplasma, Ehrlichia and Borrelia pathogens impacting human health in the USA - Madesh, Swetha (Kansas State University, 2021)
Tick-borne diseases continue to threaten the health of people, dogs, and agricultural animals. In the USA, human Lyme disease, caused by Borrelia burgdorferi, has the highest incidence, followed by diseases resulting from Ehrlichia and Anaplasma species. We investigated the prevalence of these diseases in dogs as the same pathogens are also known to cause infections in the human host. Blood samples collected from clinically suspected dogs from across the USA were assessed for antibodies for four different tick-borne pathogens. Molecular detection and culture recovery methods were also performed to detect the presence of the pathogen. A total of 1,340 samples were assessed for A. phagocytophilum, two Ehrlichia species: E. canis and E. chaffeensis, and B. burgdorferi. Positive samples included 286 (21.3%) for A. phagocytophilum, 228 (17.01%) for E. chaffeensis, 233(17.3%) for E. canis, and 366 (27.2%) for B. burgdorferi. Co-infection of A. phagocytophilum with E. canis and E. chaffeensis was observed in 64 and 65 dogs, respectively, whereas with B. burgdorferi, we observed in 76 dogs. Similarly, 34 dogs had antibodies for Ehrlichia species and B. burgdorferi. Two hundred and four dogs tested positive for the two Ehrlichia species, while eight dogs were positive for all three genera pathogens. Quantitative real-time Reverse Transcriptase PCR (qRT-PCR) was performed on 171 samples were randomly selected to assess the presence of Anaplasma phagocytophilum, Anaplasma platys, Ehrlichia canis, Ehrlichia chaffeensis, and Ehrlichia ewingii. Culture recovery experiments performed for Ehrlichia species on 66 IFA positive serum/blood did not result in any positives, and similarly, all 171 samples tested negative by molecular methods targeted to detect the bacterial DNA. We observed a significant overlap in the geographical distribution of the samples that tested positive for the pathogens belonging to all three diseases in dogs. These data are similar to the CDC-reported human prevalence data for tick-borne diseases for anaplasmosis, ehrlichiosis, and borreliosis. Our data suggest that tick-borne diseases in dogs closely resemble the prevalence data documented for humans. Thus, monitoring canine infections has important implications in serving as the sentinel species for human tick-borne diseases as well as aiding in improving the companion animal health.
Keywords: Anaplasma; Borrelia; Ehrlichia; Tick-borne diseases